Chemistry : principles and reactions ; a core text - Masterton, William L.; Hurley, Cecile N. (Fort Worth : Saunders College Publishing, 1997)
Chemistry and Physics
Keywords: Chemistry; Matter; Measurement; Atom; Molecule; Ion; Gas; Electronic structure; Thermochemistry; Electrochemistry; Nuclear chemistry; Metallurgy; Organic chemistry